Constructing and Tuning Excitatory Cholinergic Synapses: The Multifaceted Functions of Nicotinic Acetylcholine Receptors in Drosophila Neural Development and Physiology - Rosenthal, Justin S.; Yuan, Quan (Frontiers in Cellular Neuroscience, 2021)
Nicotinic acetylcholine receptors (nAchRs) are widely distributed within the nervous system across most animal species. Besides their well-established roles in mammalian neuromuscular junctions, studies using invertebrate models have also proven fruitful in revealing the function of nAchRs in the central nervous system (CNS). During the earlier years, both in vitro and animal studies had helped clarify the basic molecular features of the members of the Drosophila nAchR gene family and illustrated their utility as targets for insecticides. Later, increasingly sophisticated techniques have illuminated how nAchRs mediate excitatory neurotransmission in the Drosophila brain and play an integral part in neural development and synaptic plasticity, as well as cognitive processes such as learning and memory. This review is intended to provide an updated survey of Drosophila nAchR subunits, focusing on their molecular diversity and unique contributions to physiology and plasticity of the fly neural circuitry. We will also highlight promising new avenues for nAchR research that will likely contribute to better understanding of central cholinergic neurotransmission in both Drosophila and other organisms.